Cross cultural neighbours: exploring settler responses to the Tsawwassen Urban Treaty. - Rhodes, Catherine Deborah (2009)
This thesis examines conflict between Tsawwassen First Nation, the Host community and Delta Council representing the Settler community. The methodology is textual research and analysis of the historic and current relationship and the impact on the conflict of Delta filing a lawsuit to prevent the first Urban Treaty in British Columbia. It is a structural analysis of probable root causes of the conflict including political, economic and social linguistic barriers to understanding. The work begins with a political and policy analysis of First Nations challenges including the competing interests, fears and the public record of the Settler community. Differing worldviews, assumptions, language, core beliefs and values contribute to the walls which prevent Settlers from seeing the Host community clearly. Reconciliation or transformation of the relationship is the goal; achievable through recognizing and honouring difference. Cross Cultural Competence between the two communities is preferred to the limitations of Interest Based Negotiations.